Learning model and learning motivation on basketball learning outcomes - Putu Agus Sudiasa; I Wayan Artanayasa; Made Agus Darmadi (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
This experimental study aims to examine and prove the effectiveness of the Problem-Based Learning (PBL) model on learning outcomes, the effect of the interaction between learning models and learning motivation on learning outcomes, and the influence of learning motivation on learning outcomes. The research population is students of class X MIPA SMA Negeri 1 Sukawati for the academic year 2021-2022. The sampling technique was done by simple random sampling. Methods of data collection using test results of learning and learning motivation questionnaire. The research was divided into three activities, namely pretest, treatment, and post-test. The conclusions in this study are (1) Students who follow the PBL model get an increase in the average score of higher learning outcomes compared to students who follow the conventional learning model. (2) Higher student basketball learning outcomes are obtained by students who learn to use the PBL model, this occurs due to the advantages of the PBL model in improving student learning outcomes. (3) Basketball learning with the PBL model is proven to be better than the conventional learning model because of the compatibility between the characteristics of basketball learning and the PBL model. (4) The interaction between the learning model and learning motivation affects basketball learning outcomes